Penguatan Motivasi Belajar IPS Melalui Pemanfaatan Media Pembelajaran Gen-Smart - Achmad Dhohirrobbi; Luthfiya Fathi Pusposari (SAP (Susunan Artikel Pendidikan), 2026)
Students’ low motivation in Social Studies (IPS) at the MTs level remains a challenge due to limited instructional media and the dominance of conventional teaching methods. Although digital media have been shown to enhance learning motivation, systematically developed IPS media tailored to MTs students’ needs are still limited. This study aims to examine the effect of Gen-Smart digital learning media integrated into a blended-based experiential learning model on students’ motivation. Using a quantitative quasi-experimental design, the study involved two eighth-grade classes at MTsN 7 Malang, each consisting of 30 students assigned to experimental and control groups. The experimental class engaged in online and offline activities based on Kolb’s experiential learning stages, while the control class received conventional instruction. Data were collected through a Likert-scale motivation questionnaire administered during pretest and posttest and analyzed using normality, homogeneity, and independent samples t-tests. The findings revealed a significant difference between groups (p = 0.000 < 0.05), with the experimental class showing greater improvement in motivation. These results indicate that integrating Gen-Smart into blended learning effectively enhances students’ motivation in Social Studies.